The efficacy of mobile application use on recall of surgical risks in nasal bone fracture reduction surgery - Kim, Choong Hyeon; Cheon, Ji Seon; Choi, Woo Young; Son, Kyung Min (Archives of craniofacial surgery, 2018)
The number of surgical risks recalled by a patient after surgery can be used as a parameter for assessing how well the patient has understood the informed consent process. No study has investigated the usefulness of a self-developed mobile application in the traditional informed consent process in patients with a nasal bone fracture. This study aimed to investigate whether delivery of information, such as surgical risks, through a mobile application is more effective than delivery of information through only verbal means and a paper. This prospective, randomized study included 60 patients with a nasal bone fracture. The experimental group (n=30) received preoperative explanation with the traditional informed consent process in addition to a mobile application, while the control group (n=30) received preoperative explanation with only the traditional informed consent process. Four weeks after surgery, the number of recalled surgical risks was compared for analysis. The following six surgical risks were explained: pain, bleeding, nasal deformity, numbness, nasal obstruction, and nasal cartilage necrosis. The mean number of recalled surgical risks among all patients was 1.58±0.56. The most frequently recalled surgical risk was nasal deformity in both groups. The mean number of recalled surgical risks was 1.72±0.52 in the experimental group and 1.49±0.57 in the control group. There was a significant association between mobile application use and the mean number of recalled surgical risks ( =0.047). Age, sex, and the level of education were not significantly associated with the mean number of recalled surgical risks. This study found that a mobile application could contribute to the efficient delivery of information during the informed consent process. With further improvement, it could be used in other plastic surgeries and other surgeries, and such an application can potentially be used for explaining risks as well as delivering other types of information.